2022
DOI: 10.1002/da.23289
|View full text |Cite
|
Sign up to set email alerts
|

PTSD, major depression, and advanced transcriptomic age in brain tissue

Abstract: Background: Psychiatric disorders have been associated with advanced epigenetic age in DNA methylation, yet this relationship has not been studied in the brain transcriptome. We examined transcriptomic age using an RNA-based algorithm recently developed by Ren and Kuan ("RNAAgeCalc") and the associations between posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and alcohol use disorder with age-adjusted RNA age ("RNA age residuals") in three brain regions: dorsolateral prefrontal cortex, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In the analysis of the knowledge primed deep neural clock, we have to split the sample into a training and testing set, thus reducing our sample size to perform associations with the phenotypic traits. Still, our cohort is larger than similar to recent work 44 . Also, this reduction in sample size did not allow us to stratify the sample by sex to potential sex-specific effects.…”
Section: Limitationsmentioning
confidence: 71%
See 2 more Smart Citations
“…In the analysis of the knowledge primed deep neural clock, we have to split the sample into a training and testing set, thus reducing our sample size to perform associations with the phenotypic traits. Still, our cohort is larger than similar to recent work 44 . Also, this reduction in sample size did not allow us to stratify the sample by sex to potential sex-specific effects.…”
Section: Limitationsmentioning
confidence: 71%
“…For instance, a previous study using RNAAgeCalc identified an accelerated transcriptional age in 324 World Trade Center responders 50 . Further, an epigenetic age acceleration in the motor cortex 51 and transcriptomic age acceleration in the ventromedial PFC has been reported in PTSD cases 44 . These findings suggest that individuals diagnosed with PTSD exhibit accelerated aging, reflected at both the transcriptomic and epigenomic levels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of importance, the dysregulated inflammatory state of the elderly (also known as “inflammaging”) is a well-characterized risk factor for chronic conditions such as sarcopenia and depression [ 16 , 17 ] while genes and inflammatory pathways associated with depressive symptoms are being actively studied in the elderly. The findings revealing a link between inflammation, immune dysregulation, and accelerated cellular aging could be relevant to the association we describe [ 18 ].…”
Section: Introductionmentioning
confidence: 66%